Portraying Entrepreneurship Learning with Video Production Process Media using WhatsApp Application - Sudarwati, Ninik; Priyanto, Agus; Siyono, Siyono; Subiantoro, Hari (Universitas Negeri Surabaya, 2020)
This article is discusson entrepreneurial learning activities using WhatsApp application and entrepreneurial video media, including student responses to entrepreneurship learning in written texts enacted on WhatsApp, and the entrepreneurship learning responses in the video production process was delivered on WhatsApp. This study employed a qualitative approach. We recruited 400 students from STKIP PGRI Jombang, STKIP PGRI Nganjuk, STKIP PGRI Tulungagung, and UNWAHA to participate in the study. Findings suggested thatthe majority of the students attained sustained motivation in entrepreneurship learning. They also engaged in creative learning using video in the WhatsApp enactment. Our study calls for pedagogical decisions for teachers to employ this learning model in other classroom subjects.